A Conceptual Framework for Inclusive Semantic Retrieval in Digital Heritage Archives (Open Society Conference, 2025)
Open cultural heritage platforms like Europeana are widely used to store and share the rich history of Europe. Access to such large collections of linked data is still not widely distributed due to technical difficulties and the poor usability of semantic search interfaces. This paper proposes a conceptual framework for improving information retrieval on cultural heritage knowledge graphs. The model is built on the EDM and RDF Schema and introduces weighted semantic relationships between resources. It encodes weights as contextual metadata on edges and uses category-based weighting, external linked data sources (DBpedia, Freebase, etc. ), and optimized graph traversal to improve the relevance and inclusivity of search results. By assigning relative relevance to each graph edge based on the similarity of shared metadata categories, the proposed method increases the accuracy of query results, while improving their coverage to include semantically similar entities, allowing non-domain expert users, educators, and underrepresented communities to browse and discover new information. This work is in line with efforts to create an inclusive digital public sphere in communication studies by building on the idea of enhancing active semantic and semiotic forms of participation rather than limiting users to passive and non-inclusive forms of access. The paper is theoretical in nature, providing a proof of concept and evaluating model characteristics; however, it also briefly describes the future evaluation strategy and use cases beyond the cultural heritage context.